(untitled) (Journal of Computational Mathematics, 2003)
This is the second part of the paper for the mathematical study of nonconforming rotated Q_1 element (NRQ_1 hereafter) on arbitrary quadrilateral meshes. Some Poincarè Inequalities are proved without assuming the quasi-uniformity of the mesh subdivision. A discrete trace inequality is also proved.